Analisis Pengaruh Kepuasan Pasien Rawat Jalan Terhadap Minat Kunjungan Ulang Di Rs X Kota Madiun - Hartaty Sarma Sangkot; Ulimaz Latifah; Endang Sri Dewi Hastuti Suryandari; Avid Wijaya (Jurnal Manajemen Kesehatan Indonesia, 2022)
The patient's satisfied is an indicator that can be used to see the quality of health services. A health service can be said to be of high quality if it satisfies the expectations of the patient. Good service quality will form user commitment to reuse a service. The purpose of this study was to determine the effect of outpatient satisfaction on interest in revisits at Hospital X in Madiun City. This research is a quantitative analytic study with a cross sectional approach. This study was conducted on 100 outpatients at Hospital X in Madiun City using a questionnaire. The data collected were analyzed by univariate and bivariate. The chi square test was used in bivariate analysis. The results showed that 99% of outpatients were satisfied with the services provided and 97% of patients who were interested in making revisits. However, there was no effect of outpatient satisfaction on the interest in revisits at Hospital X in Madiun City (p Value = 1,000).